Equilibrium exchange rates in Central and Eastern Europe: A meta-regression analysis - Balázs Égert; László Halpern (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
This paper analyses the ever-growing literature on equilibrium exchange rates in the new EU member states of Central and Eastern Europe in a quantitative manner using meta-regression analysis.The results indicate that the real misalignments reported in the literature are systematically influenced, inter alia, by the underlying theoretical concepts (Balassa-Samuelson effect, Behavioural Equilibrium Exchange Rate, Fundamental Equilibrium Exchange Rate) and by the econometric estimation methods.The important implication of these findings is that a systematic analysis is needed in terms of both alternative economic and econometric specifications to assess equilibrium exchange rates.
URN:NBN:fi:bof-201408072018
Keywords: C15; E31; F31; O11; P17; 330; equilibrium exchange rate; Balassa-Samuelson effect; meta-analysis